Effectiveness Analysis of Soft Starter in Reducing Starting Current of 400 kW Three-Phase Induction Motor for Chipper Machines in the Wood Processing Industry - Savira, Resti; Abadi, Akbar; Putri, Yani Kamisa; Rahman, Aldi; Alhamda, Dinda Sukra (Departemen Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2025)
The wood processing industry heavily relies on three-phase induction motors to drive high-power equipment such as chipper machines. One of the major challenges in operating these motors is the high inrush current during startup, which can destabilize the power system and accelerate equipment wear. This study aims to analyze the effectiveness of using a soft starter as a starting method for a 400kW induction motor in a chipper application. The research method is an experimental case study involving direct field observation and theoretical calculations of electrical parameters such as nominal current, current limiting, torque, and trip class. The observation results show that the actual starting current of 1,216.15 A remains below the calculated current limiting threshold of 1,575 A, while the trip class value of 2,835 A provides optimal protection. The use of a soft starter proves effective in reducing inrush current, maintaining voltage stability, and enhancing the reliability and efficiency of motor operation. This research supports the application of soft starters as a suitable solution for high-power motor starting in heavy industrial settings.